Novel inhibitors of human glucose-6-phosphate dehydrogenase (HsG6PD) affect the activity and stability of the protein - Ramírez-Nava, Edson Jiovany; Hernández-Ochoa, Beatriz; Navarrete-Vázquez, Gabriel; Arreguín-Espinosa, Roberto; Ortega-Cuellar, Daniel; González-Valdez, Abigail; Martínez-Rosas, Víctor; Morales-Luna, Laura; Martínez-Miranda, Josué; Sierra-Palacios, Edgar; Rocha-Ramírez, Luz María; De Franceschi, Lucia; et al. (Biochimica et biophysica acta. General subjects, 2021)
The pentose phosphate pathway (PPP) has received significant attention because of the role of NADPH and R-5-P in the maintenance of cancer cells, which are necessary for the synthesis of fatty acids and contribute to uncontrollable proliferation. The HsG6PD enzyme is the rate-limiting step in the oxidative branch of the PPP, leading to an increase in the expression levels in tumor cells; therefore, the protein has been proposed as a target for the development of new molecules for use in cancer. Through in vitro studies, we assayed the effects of 55 chemical compounds against recombinant HsG6PD. Here, we present the kinetic characterization of four new HsG6PD inhibitors as well as their functional and structural effects on the protein. Furthermore, molecular docking was performed to determine the interaction of the best hits with HsG6PD. Four compounds, JMM-2, CCM-4, CNZ-3, and CNZ-7, were capable of reducing HsG6PD activity and showed noncompetitive and uncompetitive inhibition. Moreover, experiments using circular dichroism and fluorescence spectroscopy showed that the molecules affect the structure (secondary and tertiary) of the protein as well as its thermal stability. Computational docking analysis revealed that the interaction of the compounds with the protein does not occur at the active site. We identified two new compounds (CNZ-3 and JMM-2) capable of inhibiting HsG6PD that, compared to other previously known HsG6PD inhibitors, showed different mechanisms of inhibition. Screening of new inhibitors for HsG6PD with a future pharmacological approach for the study and treatment of cancer. •New chemically synthesized compounds (JMM-2, CCM-4, CNZ-3, and CNZ-7) were able to inhibit HsG6PD.•Four selected inhibitors affected the thermal stability of the HsG6PD protein.•JMM-2 and CNZ-3 affected the secondary and tertiary structure of the HsG6PD protein.•Kinetic analysis and docking studies reveal that JMM-2 and CNZ-3 do not bind to the active site.